TRIP PLANNER MOBILE APPLICATION FOR SARAWAK TOURIST WITH USING INTELLIGENT AGENT BASED DECISION MAKING ALGORITHMS - Teh, Khee Shin (Universiti Malaysia Sarawak (UNIMAS), 2020)
Tourism has emerged as a popular industry in Sarawak in recent years. Proper planning of the trip makes a trip to be unforgettable. Nowadays, technology has become an essential need in almost every aspect of our lives. The internet becomes the main source of information for user to plan the trip. The travel information in multiform for independent tourists is suf icient, but the suf icient information is not enough for making a successful itinerary planning. Tourists need to spend a lot of time on researching. Tourists hardly to get recommendation and suggestion that fir their preferences. Besides, tourists dif icult to get all the information in only one platform. There is no platform that provide event information to tourists. Thus, the proposed system which is trip planner mobile application for Sarawak tourist with using intelligent agent based decision making algorithms may help to resolve the problem. This project will enable to assists tourists to plan their trip that fit their preferences ef ectively and easily. This project will also provide event information and notification to tourists. Plus, the tourists can keep their travel itinerary in this system. The proposed system will recommend the attractions to the tourists based on their input.